Urgensi Pencegahan Dan Penanganan Kekerasan Seksual Di Uin Sunan Gunung Djati Bandung - Putri Saiba; Rivalni Oktaviani (UIN Sunan Gunung Djati Bandung, 2023)
Cases of sexual violence in tertiary institutions are increasingly sticking out, the Ministry of Religion through the Directorate of Islamic Education issued Guidelines for the Prevention of Sexual Violence in Islamic Religious Higher Education Number 5494 of 2019 but not all PTKI have followed up on this rule. UIN Sunan Gunung Djati itself has not issued PPKS SOPs as standard rules on a campus scale to deal with this. This study aims to analyze the urgency of preventing and handling cases of sexual violence at UIN Sunan Gunung Djati Bandung. This research was conducted using a qualitative descriptive method. Sources of data were obtained from the results of interview observations, analysis of regulations, articles and other related sources. The results of the observations of researchers showed that there were not a few cases of sexual violence that occurred at UIN Sunan Gunung Djati Bandung. Apart from the lack of awareness, the lack of information and outreach from the campus regarding sexual violence also makes the academic community not know what to do if sexual violence occurs on campus. WSC as an UKM directly under the auspices of the campus provides a space for reporting and assisting survivors of sexual violence through a complaint booth. But in reality the WSC runs independently and there has been no involvement from the campus. Therefore, the PPKS SOP at UIN Sunan Gunung Djati Bandung is an urgent thing to haste